The Transformation of the Gen Z Da'wah Space: An Analysis of the Himmah Community as a Platform for an Inclusive Religious Community - Ulya Qistina; Nizar Bahalwan; Khofifah Ayu Kartika; Ahmad Irfan; Siti Nuri Nurhaidah (Aimmah: Social Sciences Journal, 2026)
Urban Generation Z faces social space fragmentation and an existential crisis, creating a need for spiritual spaces that are inclusive and non-doctrinal. However, the rigidity of conventional da'wah institutions creates a psychological distance that widens the gap between their spiritual needs and available religious facilities. This study aims to examine the transformation of contemporary da'wah spaces through spatial, methodological, and cultural reconstruction, using the Himmah Community as a case study. Employing a descriptive qualitative case study design, primary data were collected through in-depth interviews with the founder and study participants, as well as participatory observation. Secondary data were obtained from a visual document analysis of Himmah's official Instagram account. Data were analyzed using thematic analysis techniques. The findings reveal three key results. First, digital branding and earth-tone visual aesthetics function as gatekeeping mechanisms that dissolve Generation Z's initial resistance to religious forums. Second, the transformation of physical space from formal institutions to residential homes—specifically, a family room without a pulpit—democratizes religious authority and fosters egalitarian, dialogical da'wah relations. Third, the integration of multisensory sessions in the form of open table after study sessions serves as an incubation vehicle for a space of belonging while simultaneously building social capital. These findings expand the discourse of the sociology of religion by affirming that the sustainability of da'wah for urban Generation Z is determined not by institutional scale, but by cultural adaptation, intimate spatial engineering, and the management of social inclusivity.